2015
DOI: 10.1007/s13197-015-1800-9
|View full text |Cite
|
Sign up to set email alerts
|

Roselle calyces (Hibiscus sabdariffa), an alternative to the food and beverages industries: a review

Abstract: The need to add value to cultivated and native plant products that have medicinal and nutritional properties is increasing due to the consumers demand. Nowadays, the bioactive compounds (phytochemicals) found in plants have many uses in the therapeutic, pharmaceutical, and food industries. Dried Roselle calyces (Hibiscus sabdariffa L.) are commercially available and appreciated to obtain concentrated extracts which might be used in the food and pharmaceutical industries. It has been shown that ingestion of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 26 publications
1
53
0
3
Order By: Relevance
“…Several advantages include the low cost of their maintenance and specialized diets as well as their easy manipulation and maintenance in controlled environmental and sanitary conditions [3,6,12,13]. Another advantage is the similarity between the oral mucosal membranes of rats and humans, which are basically made up of epithelial tissues on the surface and subjacent connective tissue called the basal lamina that provide support and nutrition to the epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several advantages include the low cost of their maintenance and specialized diets as well as their easy manipulation and maintenance in controlled environmental and sanitary conditions [3,6,12,13]. Another advantage is the similarity between the oral mucosal membranes of rats and humans, which are basically made up of epithelial tissues on the surface and subjacent connective tissue called the basal lamina that provide support and nutrition to the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The juice from its calyxes is claimed to be a health-enhancing drink because of its high contain of Vitamin C, anthocyanins [4,7,8,10,13], and protocatechuic acid [4]. Another former study reported that as an antioxidant, roselle has low bioavailability due to high acidity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations